Predictors of Pseudomonas and methicillin‐resistant Staphylococcus aureus in hospitalized patients with healthcare‐associated pneumonia. Issue 1 (8th October 2015) - Metersky, Mark L.; Frei, Christopher R.; Mortensen, Eric M.
Abstract: Background and objective: Patients with healthcare‐associated pneumonia (HCAP) are at high risk of infection with multidrug‐resistant (MDR) pathogens. Factors discriminating infection with MDR Gram‐negative (MDR‐GN) organism from infection with methicillin‐resistant S taphylococcus aureus (MRSA) are not well understood and patients are often treated for both organisms. This study was performed to determine risk factors predicting pneumonia due to P seudomonas versus MRSA. Methods: Veterans age ≥65 hospitalized with HCAP between 2002 and 2012 were identified from the Veterans Affairs administrative databases. Patients were identified with P seudomonas pneumonia, MRSA pneumonia or neither according to the International Classification of Diseases, 9th Revision, Clinical Modification codes. We assessed unadjusted and adjusted associations of patient characteristics and HCAP due to P seudomonas or MRSA. Results: Of the 61 651 patients with HCAP, 1156 (1.9%) were diagnosed with P seudomonas pneumonia, 641 (1.0%) with MRSA pneumonia and 59 854 (97.1%) with neither. MRSA pneumonia was positively associated with male gender, age >74, diabetes, chronic obstructive pulmonary disease (COPD), recent nursing home or hospital stay, recent exposure to fluoroquinolone or antibiotics treating Gram‐positive organisms, and severe pneumonia. MRSA pneumonia was negatively associated with complicated diabetes. P seudomonas pneumonia was positively associated with recent hospital stay, immunocompromise, COPD, hemiplegia, recent exposure to inhaled corticosteroids, β‐lactam/cephalosporin/carbapenem antibiotics, antibiotics against Gram‐positive organisms, 'other antibiotics' and severe pneumonia. P seudomonas pneumonia was negatively associated with age >84, higher socioeconomic status, drug abuse and diabetes. Conclusions: Patient characteristics may assist in identifying patients at risk for HCAP due to P seudomonas or MRSA. Abstract : In a large cohort of elderly veterans admitted to the hospital with healthcare‐associated pneumonia, we have identified several patient characteristics which were associated with either a higher or lower risk of diagnosis of Pseudomonas and methicillin‐resistant Staphylococcus aureus pneumonia. See Editorial, page 8